2023
DOI: 10.1371/journal.pgph.0000946
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination coverage and breakthrough infections of COVID-19 during the second wave among staff of selected medical institutions in India

Abstract: India experienced the second wave of SARS-CoV-2 infection from April 3 to June 10, 2021. During the second wave, Delta variant B.1617.2 emerged as the predominant strain, spiking cases from 12.5 million to 29.3 million (cumulative) by the end of the surge in India. Vaccines against COVID-19 are a potent tool to control and end the pandemic in addition to other control measures. India rolled out its vaccination programme on January 16, 2021, initially with two vaccines that were given emergency authorization–Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
4
4
0
Order By: Relevance
“…The majority of the healthcare professionals (69.5%) in our study had taken Covishield while 27.5% of them had taken Covaxin. Similar findings were observed in studies conducted by Rahi M et al [ 20 ] and Masthi NR et al [ 13 ], where more than four-fifths of participants had taken Covishield while a few of them had taken Covaxin. The reason behind this could be that Covishield was the first vaccine that was launched in India among front-line workers, including doctors, and another reason includes its effectiveness being seen to be more than Covaxin as seen in many studies [ 21 - 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of the healthcare professionals (69.5%) in our study had taken Covishield while 27.5% of them had taken Covaxin. Similar findings were observed in studies conducted by Rahi M et al [ 20 ] and Masthi NR et al [ 13 ], where more than four-fifths of participants had taken Covishield while a few of them had taken Covaxin. The reason behind this could be that Covishield was the first vaccine that was launched in India among front-line workers, including doctors, and another reason includes its effectiveness being seen to be more than Covaxin as seen in many studies [ 21 - 23 ].…”
Section: Discussionsupporting
confidence: 90%
“…In our study, it was observed that the incidence and severity of COVID-19 was reduced among the fully vaccinated healthcare workers even during rising cases of Delta and Omicron variants in the district and this finding was similar to most of the contemporary and recent studies. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The Incidence of COVID-19 vaccine breakthrough infection among healthcare workers in our study was 7.9% in a year observation period which was similar to a study done by Paris et al with 4.4% over six months, Rahi et al at 8.7% and De Maria et al at 9.7% over one year and 20.2% over 2 years. 17,19,26,27 In studies done by Gurung et al and Bhavya et al, there was a significantly higher incidence of COVID-19 vaccine breakthrough infections among healthcare workers compared to our study which could be partly explained by increased awareness, better adherence to COVID-19 appropriate behaviour in our study and possibility of highly transmissible variants circulating among the participants of their study.…”
Section: Discussionsupporting
confidence: 87%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] The Incidence of COVID-19 vaccine breakthrough infection among healthcare workers in our study was 7.9% in a year observation period which was similar to a study done by Paris et al with 4.4% over six months, Rahi et al at 8.7% and De Maria et al at 9.7% over one year and 20.2% over 2 years. 17,19,26,27 In studies done by Gurung et al and Bhavya et al, there was a significantly higher incidence of COVID-19 vaccine breakthrough infections among healthcare workers compared to our study which could be partly explained by increased awareness, better adherence to COVID-19 appropriate behaviour in our study and possibility of highly transmissible variants circulating among the participants of their study. 16,18 On the contrary, several studies showed a lesser incidence of COVID-19 vaccine breakthrough infection among healthcare workers when compared with our study.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The disease-modifying nature of COVID-19 vaccines has been shown by various researchers, where only mild to less severe infections occurred in vaccinated individuals [ 13 , 21 , 23 ]. Doke et al studied patients with BTI in two hospitals in Pune and concluded that replication of the virus is reduced in vaccinated individuals because of the immediate rise in immune response and high levels of neutralizing antibodies during BTI [ 13 ].…”
Section: Discussionmentioning
confidence: 99%